Pemanfaatan Hasil Biokonversi Limbah Organik sebagai Pupuk Organik Cair untuk Pertumbuhan Tanaman Miana - Noor Hayati, Rina; Chandra S. Rahendaputri; Ariani, Ismi Khairunnissa; Dellangi, Inri Lestari (LPPM ITK, 2025)
Efforts to reduce organic waste can be done by recycling waste through utilization into liquid organic fertilizer. One of the efforts to process organic waste can be done by Black Soldier Fly (BSF) maggot. This study was conducted with the aim of seeing the ability of liquid organic fertilizer (POC) produced from leachate from bioconversion carried out by BSF, on the growth of miana plants (Plectranthus scutellarioides). This research is an experiment with qualitative and quantitative data analysis methods. The research was conducted by giving two different POCs. Sample A used 100% commercial organic fertilizer and sample D used POC with a ratio of bioconverted organic fertilizer to commercial liquid fertilizer (3:1). Both samples still could not meet the quality standards of nutrients (NPK) and C-organic. However, the sample with the ratio of bioconverted organic fertilizer and commercial liquid organic fertilizer (3:1) or sample D is the optimum sample, with nutrients (NPK) reaching 0.438% and C-organic reaching 4.58%. The results of the application proved that plants with sample D showed the best growth in terms of the number of leaves that reached 14 strands and plant height reached 13 cm in week 8.